Stanum dioxide (SnO2) doped polyaniline (n-C6H5NH2) thin film as the materials for liquefied petroleum gas (LPG) and hydrogen (H2) gas sensor - Nur Amirul Mukmin, Endut (2009)
Gas sensor is a device which detects the presence of gas. The choice in selecting gas sensor was based on their sensitivity, selectivity and stability. The objectives of this research are to study stanum dioxide (SnO2) doped polyaniline (n-C6H5NH2) as new sensing materials for LPG and H2 gas sensor at room temperature and to study the gas (LPG and H2) sensing characteristic to the sensor at room temperature. This research focused on the effect of doping ratio of sensor material, gas flow time to the gas response and response time of the sensor. Sensors are prepared using two deposition methods which are chemical bath deposition (CBD) for fabrication of SnO2 and electrodeposition (ED) for fabrication of polyaniline. In this experimental work 3 sensors with different doping ratio (polyaniline: SnO2) were prepared which is 70:30, 50:50 and 30:70. The gas response most influenced by the doping ratio. From the result the highest gas response (55%) achieved by sensor with doping ratio 70:30 for LPG contrast with highest gas response (50%) for H2 achieved by sensor with doping ratio 30:70. The response time most influenced by gas flow time. High flow time means the concentration is high. Based on experimental result at range 10s to 40s of gas flow time, the 40s gas flow time show the short time response for all sensor.